PRECISE RE-OS DETERMINATIONS AND SYSTEMATICS OF IRON METEORITES - Shen J.J.; Papanastassiou D.A.; Wasserburg G.J. (My University, 1996)
The Re-Os system for samples of FeNi, sulphide, and phosphide from iron meteorites was investigated. Techniques were developed which yield reproducible analyses for Re/Os at the 2%‰ level and which permit complete isotopic exchange between sample and tracer, as is necessary for concentration measurements of Re and Os by isotope dilution. High precision osmium and rhenium isotope data have been obtained using negative ion thermal ionization, with ionization efficiencies of up to 10% for Os and 20% for Re, both for normals and for Re and Os extracted from the samples. Replicate analyses of Re/Os are in good agreement, within ±2.5%o. The results show a well defined correlation line on a 187Re-187Os evolution diagram for iron meteorites from groups IAB, IIAB, IIIAB, IVA, and IVB, all taken together. This correlation line yields a slope of 0.07863 ± 0.00031 (2σ) and initial 187Os/188Os = 0.09560 ± 0.00018 (2σ). If the individual groups of iron meteorites for which there is sufficient dispersion in Re/Os are considered, data on the IIAB and on the IVA irons appear to indicate a difference in age of 60 ± 45 Ma, with the IVA group being older. This age difference is qualitatively the same as obtained for Pd-Ag data but is larger. Sulphides from two IAB iron meteorites show extremely low concentrations of Re and Os and indicate that Re and Os are not partitioned into this phase during planetary differentiation. There is evidence for recent element remobilization or contamination, corresponding to relative enrichment of Re or loss of Os in the sulphides. Schreibersites contain small but significant amounts of Re and Os, with high Re/Os relative to the metal phases and with 187Os/188Os much more radiogenic than in the metal. Model ages for the Schreibersites are relatively young (4.3–3.5 AE) and indicate that the Schreibersites were open-systems for Re-Os at least 0.5–1 AE after the original formation of the iron meteorites. It now appears possible to use metal- schreibersite pairs to determine internal isochrons. Based on the schreibersite model ages, the cooling rates for the two IAB meteorites are estimated to be ∼ 1°C/Ma, more than an order of magnitude lower than the most recently determined metallographic cooling rates for IAB irons (Herpfer et al., 1994).